Long term efficacy of a pre-erythrocytic malaria vaccine and correlates of protection in children residing in a malaria endemic country - Olotu, A (2013)
Malaria remains an important cause of morbidity and mortality among children in sub-Saharan Africa despite recent reductions in malaria incidence in some parts of Africa. Current control tools face threats such as the emergence of drug resistant parasites and insecticide resistant mosquitoes. A malaria vaccine is needed to complement and/or replace existing tools in order to achieve better malaria control and eventually eliminate the disease. RTS,S/AS01E is the most clinically advanced pre-erythrocytic malaria vaccine candidate and is currently being tested in a phase III trial. The short-term efficacy of RTS,S/AS01E is known but the duration of protection is unknown. Furthermore, although RTS,S is protective, it is unclear which immunological assays predict efficacy: hence there are no known correlates of vaccine-induced protection against clinical malaria. In a randomized controlled trial, I assessed the efficacy of RTS,S/AS01E in children (5-17 months old) residing in Kilifi, Kenya, over 4 years of follow-up and determined the correlates of protection against clinical malaria. In order to examine the effect of variations in malaria exposure on vaccine efficacy, I developed an individual marker of malaria exposure calculated as distance-weighted prevalence of malaria infection within 1 km radius of every child. Over 4 years of follow-up, RTS,S/AS01E had an efficacy of 29.9% (95%CI: 10.3% to 45.3%, p=0.005) and 16.8% (95%CI: -8.6% to 36.3% p=0.18) against first and all malaria episodes, respectively (by intention to treat analysis). Vaccine efficacy waned over time and with increasing malaria exposure. RTS,S/AS01E efficacy was 43.6% (95% CI, 15.5 to 62.3) in the first year but was -0.4% (95% CI, -32.1 to 45.3) in the fourth year. Vaccine efficacy was 45.1% (95%CI 11.3% to 66.0%) among children with lower than average malaria exposure index, but 15.9% (95%CI -11.0 to 36.4%) among children with higher than average malaria exposure index. Despite waning in efficacy, RTS,S/AS01E averted 65 cases of malaria per 100 vaccinated children, with more cases averted among the children in the higher malaria-exposure cohort (78 cases per 100 vaccinated children) than those the low exposure cohort (62 cases per 100 vaccinated children). RTS,S/AS01E induced high titres of anti-CS protein antibodies and CD4+ T cell but not CD8+ T cell responses. Anti-CS antibody titres and the frequency of TNF-α producing CD4+ T cell responses were independently associated with protection from clinical malaria, and the combination of both anti-CS titers and TNF-α producing CD4+ T cell response satisfied the Prentice criteria for surrogate markers of protection. There was no association between avidity of RTS,S-induced anti-CS protein antibodies and protection from clinical malaria. Conclusions: RTS,S/AS01E efficacy against all episodes is 16.8% over the 4 years of follow-up. The vaccine efficacy wanes over time and with increasing malaria exposure. RTS,S/AS01E-induced TNF-α producing CD4 T cell and anti-CS protein antibody responses were independently associated with protection from clinical malaria. Anti-CS avidity did not predict protection from clinical malaria. Long-term follow-ups of malaria vaccine trials are essential in the evaluation of the longevity of vaccine efficacy.